Pressão do tempo e falta de informação: a influência na qualidade da decisão - Corso, Kathiane Benedetti (2009)
This study aimed to verify how time pressure and missing information influence the quality of decisions. Themes investigated were decision process; its influential factors - time pressure and missing information; quality of the decision; and Multicriteria Method AHP - Analytical Hierarchical Process. To achieve the proposed objective was developed a Decision Support System - the AHP MAKH-ER structured with the AHP method. Once validated by users and the researcher, an experimental research was done using a decision task with multiple alternatives and criteria, with twenty subjects divided into four experimental groups, according to the incidence or not of the time pressure and the missing information. The task which simulates a car purchase was structured to create an environment for decision, in which knowledgeable individuals from car industry make their choices and comparisons, whether or not subjected to time pressure and missing information. Formulated and tested the hypothesis it was verified that (a) the time pressure does not influence negatively the quality of individuals‟ decisions, (b) the missing information does not influence negatively the quality of individuals‟ decisions, and (c) further information does not overcome the lack of time to decide, thus not improving the quality of individuals‟ decisions. However, it was also possible, through a post-experiment questionnaire and the mapping of computer access (logs) to verify different behaviors of individuals in decision making. Pressured by time the individuals sought the information by criteria, or, changed their strategy: starting by the alternative and subsequently by the criterion. The experimental subjects, facing the time pressure focused on the car of their choice, whereas without time pressure, they rationalized some more, using the information, and disagreed with the car chosen. Assumptions of the Theory of Image also explained some findings, indicating that previously structured images in the mind of the decision maker, which represent his preferences, are a way to face the time pressure. Still regarding this variable, it was found that the decision-makers accelerate the processing of information, making the task more quickly and thus they feel more the pressure of time, as blocking of the mind and feeling of stress, then the missing information when subjected to both variables. Upon the missing information it was observed that the use of prior knowledge and experience was the most prominent strategy of confrontation. In a lower frequency, there was also a demonstration of confidence by some experimental subjects when information was missing in the task. Finally, a strategy observed was the choice of the alternative in which information was available (when compared with other alternative without information), emphasizing that this topic needs a greater depth.